Substitution of Soybean Meal with Distiller’s Dried Grains with Solubles and Its Effect on Physical Parameters of Broiler Diets - Kumar, Sushil; Sihag, Zile Singh; Sihag, Sajjan; Singh, Narender (Indian Journal of Animal Nutrition, 2017)
Effect of replacement of soybean meal (SBM) with distillers dried grains with solubles (DDGS) along with supplementation of the lysine on the physical parameters of the broiler diets was determined. DDGS was added at 15, 30 and 45% along with lysine at the level of 0, 0.50, 0.75 and 1% to each DDGS based diet. The bulk density of diets with 45% replacement of SBM with DDGS was higher (P